IMPLEMENTASI PROGRAM TEACHING FACTORY DALAM MENINGKATKAN KETERAMPILAN KEWIRAUSAHAAN PADA SISWA KELAS XI PROGRAM KEAHLIAN TEKNIK BISNIS DAN SEPEDA MOTOR (TBSM) DI SMK KRIAN 2 SIDOARJO - Marshanda Aprilia; Supriyanto Supriyanto; Ainur Rifqi; Nuphanudin Nuphanudin; Kaniati Amalia (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the implementation of the Teaching Factory program in improving the entrepreneurial skills of 11th grade students majoring in Business and Motorcycle Engineering at SMK Krian 2 Sidoarjo. This study uses a qualitative approach with a case study design. Data Collection was conducted through observation, semi-structured interviews, and documentation, then analyzed using the Miles, Huberman, and Saldana model with triangulation of sources and techniques to maintain data validity. The results showed that the implementation of the Teaching Factory through AHASS workshop services provided students with real entrepreneurial experience, as demonstrated by their active involvement in workshop management, communication with customers, and the application of industry work standards. The application of the block scheduling system provides intensive support to students, while the habit of industrial work culture such as discipline, work ethic, communication, and teamwork contributes to the formation of students’ professional attitudes and entrepreneurial skills. This study confirms that the integration of the Teaching Factory, block system, and industrial work culture effectively improves the entrepreneurial skills of automotive vocational school students.